2017
DOI: 10.18632/oncotarget.16767
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic targeting of EGFRvIII/PDK1 axis in temozolomide resistant glioblastoma

Abstract: Glioblastomas are characterized by amplification of EGFR. Approximately half of tumors with EGFR over-expression also express a constitutively active ligand independent EGFR variant III (EGFRvIII). While current treatments emphasize surgery followed by radiation and chemotherapy with Temozolomide (TMZ), acquired chemoresistance is a universal feature of recurrent GBMs. To mimic the GBM resistant state, we generated an in vitro TMZ resistant model and demonstrated that dichloroacetate (DCA), a metabolic inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…Interestingly our results showed that TMZ-induced apoptosis is not associated with changes in Bcl-2, Bcl-XL, Mcl-1, and Bax expression in RH30 and C2C12 cell lines. It has been previously reported that TMZ-induced apoptosis decreases mitochondrial membrane potential in glioma cell line 78 , 79 while our results showed that TMZ-induced apoptosis had not affected the mitochondrial membrane potential in both RH30 and C2C12 cells. This observation can be explained by our finding that TMZ has not affected the expression of anti-apoptotic (Bcl-2, Bcl-XL, and Mcl-1), and pro-apoptotic (Bax) Bcl-2 family proteins.…”
Section: Discussioncontrasting
confidence: 49%
“…Interestingly our results showed that TMZ-induced apoptosis is not associated with changes in Bcl-2, Bcl-XL, Mcl-1, and Bax expression in RH30 and C2C12 cell lines. It has been previously reported that TMZ-induced apoptosis decreases mitochondrial membrane potential in glioma cell line 78 , 79 while our results showed that TMZ-induced apoptosis had not affected the mitochondrial membrane potential in both RH30 and C2C12 cells. This observation can be explained by our finding that TMZ has not affected the expression of anti-apoptotic (Bcl-2, Bcl-XL, and Mcl-1), and pro-apoptotic (Bax) Bcl-2 family proteins.…”
Section: Discussioncontrasting
confidence: 49%
“…In fact, Koukourakis et al sensitized glioblastoma cell lines, namely the most resistant ones, to conventional therapies (radiotherapy and chemotherapy with TMZ), using the glycolytic inhibitor 2‐DG and the LDHA inhibitor oxamate, as well as LDHA gene silencing. Velpula et al also demonstrated that other mechanisms than MGMT expression can be involved in MDR phenotype, namely in glioblastomas. The authors observed that DCA increases TMZ cytotoxicity, reverting the Warburg effect through tyrosine kinase signalling, namely via EGFRvIII.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigate the features of drug-resistant tumor cells in vitro frequently employ long-term culture of tumor cells, where slowly increasing concentrations of a given drug are repeatedly added over the course of weeks or many months [ 3 , 4 , 5 , 6 , 7 ]. In the in vivo situation, or in patient tissues, as well, when before-and-after specimens are being compared, the samples usually differ by many cycles of drug treatment [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%